SEJARAH DAN PERKEMBANGAN MAJALAH MATAN SURABAYA TAHUN 2006-2018 - Frisca Rachmadani (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2020)
Abstract: This article examines the history of the development of Matan Magazine in Surabaya in 2006-2018. The problems discussed in this study are: 1) What is the background for the publication of Matan Magazine in Surabaya 2) How is the development of Matan Magazine in Surabaya 3) What are the supporting and inhibiting factors for Matan Surabaya Magazine? The writing of this article was compiled using historical research methods by taking the steps of Heuristics (Source Gathering), Verification (Source Criticism), Interpretation (interpretation of sources, and Historiography (historical writing). While the approach used is a historical approach and uses the theory of continuity and change Continuity and change theory according to John Obert Voll is continuity/sustainability and change From the results of the research conducted it can be concluded that: 1) Matan Magazine was published on the recommendation of the 13th Muhammadiyah Regional Conference in the city of Madiun in 2005. This recommendation was given because Suara magazine Muhammadiyah, which is based in Jogjakarta, cannot reach remote areas. 2) The development of Matan Magazine can be seen in terms of rubric development, circulation development, distribution development, and sources of funds. 3) In its development so far Matan magazine has not been separated from supports or obstacles. Keywords: magazine, Muhammadiyah, Surabaya